Takhrij and Syarah Hadith of Chemistry: The Use of Soil Soap to Sanctify Mughallazah Unclean - Sofia Kirana; Hanameyra Pratiwi; Assyifa Junitasari; M. Yusuf Wibisono; Munir Munir (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet Saw. about the use of soil as purification mughallazah unclean. This research method is qualitative through the takhrij and syarah hadith approaches with chemical analysis. The results and discussion of this study is that the components contained in the soil can clean and adsorb bacteria from dog saliva. The conclusion of this research is takhrij and syarah hadith of the Prophet Saw. regarding the use of soil as a purifier for mughallazah unclean with chemical analysis it is proven that bacteria or viruses in dog saliva can be absorbed by the soil.